Pertubuhan Arkitek Malaysia (PAM) Centre / Muhammad Akmal Sugeng Triwahyono ... [et al.] - Muhammad Akmal, Sugeng Triwahyono; Luqman Hakim, Zulkarnain; Nurnadia Syakireen, Mohamed Rosli; Nurul Anis Sahira, Mohamed Zainuddin (2019)
An Integrated Final Project (IFP) is the most important subject among all other subjects throughout 6 semesters (including practical training) in Diploma level of building surveying department students. Students have to form into groups and need to do a research on the maintenance organization/company management in the selected building which listed throughout various of categories. The students need to relate their findings with their own knowledge in how to build a well maintenance organization. At the end of the research, students would be able to determine the strength & weaknesses of the organization that may emphasis to the property maintenance management. This Integrated Final Project consists of 9 chapters which tell us detailed more about the maintenance organization/company in the selected building on every kind of aspects. Starting from chapter 1, which focus more about the detail of the property from the name, year of built, the facilities & services used in the building and the location and its adjacent buildings. In chapter 2, we will discuss more about the maintenance organization such as the organization structure of the company and more about their scope of work & responsibility of every worker from the personnel to the general manager. In chapter 3, we will go through the maintenance programme of the case study and how it is done and when its interval. Next in chapter 4, we will go through detailed about the building services from the electrical system, water supply system, mechanical ventilation system, and many much more system that consist in a building. We will also go through the design and the concept on the selected case study. In chapter 5, we will focus on the building condition survey of the building where we identify the overall rating for the building based on the building’s condition and given estimated cost for every remedial works for the building defects. Furthermore, in chapter 6, we able to discover the maintenance strategy for the maintenance organization/company on how it is done to have a good and efficient maintenance work by the organization whether it is throughout key performance index, benchmarking & penalty charges for inefficient work. In chapter 7, we will discuss on the legal aspect where the building is really complying to By-Law in every kind of aspects from the structure itself to their safety for occupants. We also go through on the tenancy agreement for the tenants in the building and their service contracts. In chapter 8, We will focus more the financial aspects of the maintenance organization/company on how the income and expenditure goes with the flow every year and we also do a budget forecast for 3 years in future in order to see the efficiency of cash flow and financial management. Lastly, in chapter 9, it concludes the overall research in order to summarize the understanding of the students on their case study and how well did they really know the information on the maintenance organization. We will also include the problems & recommendation that tell us the problems in the building and ways to improve one.